Cross-species analysis of abiotic stress in hydroponic leafy crops reveals conserved regulatory networks and key divergences - Lee, Jia Min; Goh, Jong Ching; Koh, Eugene; Mutwil-Anderwald, Daniela; Mutwil, Marek (Frontiers in Plant Science, 2025)
Hydroponics is emerging as a vital method for producing resilient leafy greens in controlled environments. To systematically capture how hydroponically grown crops respond to stress, we subjected three species—cai xin, lettuce, and spinach—to 24 environmental and nutrient treatments. Growth measurements showed that extreme temperatures, reduced photoperiods, and severe macronutrient (N, P, K) deficiencies significantly limit fresh weight. Transcriptomic profiling (276 RNA-seq libraries) highlighted strong, shared downregulation of photosynthesis-related genes and upregulation of stress response and signaling genes across all three species. Leveraging a novel pipeline that merges regression-based gene network inference with orthology, we identified highly conserved gene regulatory networks (GRNs) spanning all three species—marking the first cross-species analysis of stress-responsive GRNs in economically important hydroponic leafy vegetables. These networks are anchored by well-known transcription factor families (e.g., WRKY, AP2/ERF, GARP), yet show lineage-specific differences compared to Arabidopsis, suggesting partial divergence in key regulatory components. Lastly, we introduce StressCoNekT (https://stress.plant.tools/), an interactive, publicly available database that hosts our transcriptomic data and offers comparative tools to accelerate the discovery of robust stress-responsive genes and cross-species analysis. This study not only deepens our understanding of abiotic stress adaptation in hydroponic systems but also provides a critical foundation for breeding stress-resilient crops and developing smart agriculture solutions.